Swim test for joint angles dispersion analysis during hind limb motor function assessment in SCI models - Smirnov, Vladimir A.; Bazanovich, Sergey A.; Yadgarov, Mikhail Ya.; Zvyagintseva, Marina A.; Grin, Andrew A.; Ryabov, Sergey I. (Journal of Experimental Sciences, 2021)
In the most of functional studies, various stress tests are used to assess functional improvement following spinal cord injury in animal models. However, available methods of motor function evaluation are not always accurate and unbiased. The main objective of the study was to create a new method of motor activity assessment in minor animal models of spinal cord injury. This method should provide an objective and accurate evaluation of limb motor function in models having severe neurological disorders following contusion spinal cord injury. The swimming test was used as the key behavioral test. To assess the motor function of swimming animals’ hind limbs, we measured angles of hind limbs movements adjusted to the motion direction axis. Then we calculated individual angles dispersion for each joint and limb using the parameters of angles sample dispersion and amplitude-depending dispersion. The current study included two groups of Sprague-Dawley rats: control group and a group of animals having moderate thoracic spinal cord contusion injury. Control animals demonstrated stable dispersion indicators for 6 weeks of follow-up. In the experimental group, a tendency to the improvement of motor function in hind limbs between 1 and 3 weeks was revealed followed by stabilization and preservation of both indicators between 3 and 6 weeks. Provided method based on the measurement of joint angles adjusted to the movement direction axis followed by calculation of indicators of variance of a random variable and amplitude-depending variance can be an effective and objective alternative for motor function evaluation.